Retention of women architectural engineers in industry - Keen, Julia (Kansas State University, 2010)
Retention of women in the architectural engineering workforce is important to the diversity and future success of the profession. However, little research has been done on why women leave the engineering workforce, making it difficult for engineering employers to accommodate the needs of women employees as a means of increasing retention. This research study identifies the retention rate of women in architectural engineering and determines why women leave the profession. The study consisted of a written survey coupled with follow-up telephone interviews only with those who completed the survey and were no longer employed. A mailed survey was sent to all female graduates between the years 1990 and 2005 from a Midwest state university architectural engineering program. Individual telephone interviews were then conducted with these women who had identified themselves as no longer employed in a field related to architectural engineering. The study revealed a retention rate of 66%. It did not identify one single factor as the reason women leave the architectural engineering workforce but rather many factors that seem to contribute to or influence this decision. The primary factors that surfaced included work environment, family/work balance, and mentoring. These factors influencing retention are consistent with prior research on this topic in engineering and architecture. Four recommendations specifically promote retention in response to these findings: 1) offer alternate working arrangements to better accommodate family responsibilities, 2) develop mentoring programs to support female employees in their career progression, 3) develop programs to discuss issues that are specific to women in a male dominated workforce to help women be better equipped for obstacles they may encounter during their career progression, and 4) promote and assist women to re-enter the workforce, recognizing that some women will make the choice to take a break from their career.
Keywords: Retention; Engineering; Women; Workplace; Architectural engineering; Gender; Engineering, General (0537)